Numerical simulation method of the failure behavior of the UMo-Al monolithic fuel element - Zheng, Zhifeng; Peng, Shinian; Liu, Yu; Wu, Xiaoli; Sun, Hongping; Xin, Yong; Deng, Jian (Frontiers in Energy Research, 2024)
The UMo-Al monolithic fuel element has a special failure mode of blistering on the cladding surface under high temperature and high burn-up conditions. In order to provide an auxiliary means for the safety analysis and failure limit formulation of the fuel element, this study establishes a numerical simulation method of fuel failure behavior, considering the fracture behavior and the fission gas pressure acting on the cracks for the UMo-Al monolithic fuel element. Numerical simulation is based on ABAQUS software and the extended finite element method (XFEM), established by programming FORTRAN subroutines UMAT, UMATHT and UAMP and using the thermo-mechanical sequential coupling method. Combined with Python to secondary develop ABAQUS with FORTRAN subroutine, this study realizes the coupling of fission gas pressure load and crack propagation. This study obtained the failure threshold temperature, blistering height, area and other blistering characteristics of the UMo-Al monolithic fuel element through numerical simulation of annealing experiments on L1P460 in RERTR-12. Comparison of the numerical simulation results with RERTR-12 experiment shows that the method established in this study can effectively analyze blistering failures.